ANALISIS KINERJA PELAKSANAAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) PEMERINTAH KABUPATEN TANA TORAJA - Bonilisa Rantebalik; Tawakkal Tawakkal; Anna Sutrisna S (FEB Universitas Sultan Ageng Tirtayasa, 2016)
This research was conducted to analyze the implementation performance Regional Revenues and Expenditures Budget of Tana Toraja sLocal Government during the 2010-2014 period with three performace approach consist of Revenues, Expenditures, and Financing. Analyze method used in this research is descriptive with qualitative approach and quantitative approach. The results showed that the performance of Regional Revenues and Expenditures Budget Tana TorajaLocal Government during the 2010-2014 period generally is quite good.The Budget performance based on revenues approach is good with positive revenues growth and local real revenues during the 2010-2014 period could realized more than the expectation which is covered on budget. The Budget performance based on expenditures approach, there are some programs which is not realized maximal, besides that the allocation of budget utilization focused on goverment daily activity. Based on Fincing sector, showed that positive performance of SILPA growth so it means that appropriately budget presentation by local government. Penelitian ini dilakukan untuk menganalisis kinerja pelaksanaan Anggaran Pendapatan dan Belanja Daerah Pemerintah Daerah Tana Toraja selama periode 2010-2014 dengan tiga pendekatan performansi yang terdiri dari Pendapatan, Pengeluaran, dan Pembiayaan. Metode analisis yang digunakan dalam penelitian ini adalah deskriptif dengan pendekatan kualitatif dan pendekatan kuantitatif. Hasil penelitian menunjukkan bahwa kinerja Anggaran Pendapatan dan Belanja Daerah Kabupaten Tana TorajaPemerintah Lokal selama periode 2010-2014 umumnya cukup baik. Kinerja anggaran berdasarkan pendekatan penerimaan baik dengan pertumbuhan pendapatan positif dan pendapatan asli daerah selama periode 2010-2014 dapat menyadari lebih dari harapan yang tercakup dalam anggaran. Kinerja anggaran berdasarkan pendekatan pengeluaran, ada beberapa program yang tidak terealisasi maksimal, disamping itu alokasi penggunaan anggaran terfokus pada kegiatan harian pemerintah. Berdasarkan sektor Fincing, menunjukkan bahwa kinerja pertumbuhan SILPA positif sehingga ini berarti presentasi anggaran yang tepat oleh pemerintah daerah.